Pemanfaatan smartphone dan motivasi belajar terhadap prestasi belajar - Sri Wahyuni; Dea Vivianti; Penni Ani Simanungkalit (Sekola Tinggi Teologi Sangkakala Jakarta, 2023)
Abstract This research aims to determine the impact of smartphone use and student learning motivation in achieving learning achievement at STT Sangkakala Jakarta. The hypothesis put forward is: